The Economics of Cyberattacks on Brazil. - Kshetri, Nir; DeFranco, Joanna F. (Computer (00189162), 2020)
Cyberattacks have significant economic, political, and privacy-related impacts in Brazil. Regulatory and enforcement measures have been insufficient to prevent these attacks. The authors analyze these trends and assess some recent measures to address these issues.